Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jpcc.6b00589
|View full text |Cite
|
Sign up to set email alerts
|

Surface Acid–Base Properties of Anion-Adsorbed Species at Pt(111) Electrode Surfaces in Contact with CO2-Containing Perchloric Acid Solutions

Abstract: Abstract:Carbonate and bicarbonate adsorption on Pt(111) electrodes from CO 2 saturated acidic solutions is investigated by cyclic voltammetry and Fourier Transform Infrared Reflection Absorption Spectroscopy (FT-IRRAS). Spectroscopic results show carbonate and bicarbonate adsorption even at pH=1, where bulk concentration of these anions is negligible. Moreover, analysis of the potential dependence of band intensities corresponding to adsorbed carbonate and bicarbonate reveals an effect of the electrode potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…The specific nature of the electrolyte could be also acting as a regulating agent of the interfacial pH . Ayemoba and Cuesta used attenuated total reflection surface‐enhanced infrared absorption spectroscopy (ATR‐SEIRAS) to investigate the specific role of the alkaline cation (Li, Na, K, Cs) in the CO 2 RR on gold electrodes .…”
Section: Structure Sensitivity In Co2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific nature of the electrolyte could be also acting as a regulating agent of the interfacial pH . Ayemoba and Cuesta used attenuated total reflection surface‐enhanced infrared absorption spectroscopy (ATR‐SEIRAS) to investigate the specific role of the alkaline cation (Li, Na, K, Cs) in the CO 2 RR on gold electrodes .…”
Section: Structure Sensitivity In Co2 Reductionmentioning
confidence: 99%
“…[103] The specific nature of the electrolyte could be also acting as a regulating agent of the interfacial pH. [112] Ayemoba and Cuesta used attenuated total reflection surface-enhanced infrared absorption spectroscopy (ATR-SEIRAS) to investigate the specific role of the alkaline cation (Li, Na, K, Cs) in the CO 2 RR on gold electrodes. [107] Local changes of the interfacial pH were calculated from the relative intensity of both CO 2 and HCO 3 À IR bands, assuming that both species were in equilibrium.…”
Section: Electrolyte Effects: Role Of Ph and Specific Adsorptionmentioning
confidence: 99%
“…3. Plots of (= log[f/ (1f)] vs E extracted from the spectroscopic data (scattered symbols) reported by Martinez-Hincapie et al [1] The solid lines were obtained from the application of the Smith and White model [2] for optimized values of the parameters involved. i.e.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…In a recent paper, Martinez-Hincapie et al [1] reported in situ reflection-absorption Fourier transform infrared spectra for a Pt(111) electrode in CO2-saturated KClO4/HClO4 aqueous solutions of pH values ranging from 0.38 to 3.10 as a function of the applied potential, E. Quantitative analyses of the data collected revealed significant changes in the relative ratios of the integrated intensities of the peaks, and thus in the coverage of adsorbed bicarbonate, , and carbonate, , with both E and pH. Shown in scattered symbols in Fig.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation